الخط العربي نشأته و تطوره في العصر العثماني - بلال أحمد بيغ (Journal of Calligraphy, 2022)
The first calligraphy style developed during the end of the 7th century. Called Kufic, it was named for the city of Kufa in southern Iraq and was based on early 3rd- or 4th-century Arabic scripts. It was the first calligraphy used for the Quran, though it wasn't easy to use when writing long texts. It had angular letters with short vertical strokes and long horizontal strokes. Over time, many other calligraphic styles developed in the Muslim world. Some were used for specific purposes. Some were highly decorative. Others were easy to read, which made them appropriate for books and documents.The other script included Naskh or Naskhi, a script that developed in the 10th century that was easily readable with small balanced letters made from curving, fluid lines. Naskh eventually replaced Kufic as the script of choice for the Quran.